Ćwiczenia z empatii. Wieloryb The Globe w reżyserii Evy Rysovej i Ostatnie zwierzęta w reżyserii Magdy Szpecht w Teatrze Łaźnia Nowa w Krakowie - Filipowicz, Anna; Jazgarska, Anna (Zoophilologica. Polish Journal of Animal Studies, 2018)
The performances: Wieloryb The Globe and Ostatnie zwierzęta show the whole scale of difficulties that accompany the entering into ethical relationships with the Other. From the point of view of traditional culture, making them is a story of stumbles, mistakes and errors that result in an uncertain encounter at best. The “exercises in empathy” designed by these performances are oriented towards the bottom-up emancipation of the excluded beings, both human and non-human once. According to their creators, it is possible only through education, not through revolution.